Physiological and behavioural response of two dairy cows’ genotypes during summertime in the central region of Chile - Arias, Rodrigo A.; Herrera, Camila; Larraín, Rafael; González, Fernando; Mader, Terry L.; Velásquez, Alejandro (Austral Journal of Veterinary Sciences, 2018)
Heat stress has been recognised as a serious problem in dairy farms. The study goal was to assess the effects of climatic conditions on physiological and behavioural responses of dairy cows in Central Chile. Data of tympanic temperature (TT), panting score, respiration rate (RR), and shade utilization of cows from two genotypes, Holstein (H) and Holstein x Montbeliarde (HM), were collected twice per day (AM/PM) during three periods of the summer season in Central Chile. Moreover, three thermal comfort indices: Comprehensive climate index (CCI), temperature humidity-index (THI), and adjusted THI were estimated using meteorological data. The hour of each day was classified as “Normal” or “Stressful” based on CCI threshold of 25 °C. Statistical analysis included ANOVA, repeated measures analysis and Chi square test (α=0.05). There was an interaction of genotype x CCI condition x period (P=0.0026) with the highest TT of both genotypes under a stressful condition within each period. In addition, interactions of genotype x hour (P<0.0001) and genotype x CCI condition (P<0.0002) were also observed. The HM cows showed greater TT than H cows in both CCI conditions. The RR was higher during the afternoon and a greater proportion of cows used shade at “Mild” and “Moderate” CCI categories (P<0.001). Both genotypes showed some degree of heat stress, but cool nights and shade seem to be enough to allow to cows’ cope with the challenging diurnal conditions observed in the summer season. A study of these effects on milk production is necessary to confirm or discard the previous.